2005
DOI: 10.1089/jam.2005.18.55
|View full text |Cite
|
Sign up to set email alerts
|

A Prototype Prophylactic Anti-Influenza Preparation in Aerosol Form on the Basis ofAbies sibiricaPolyprenols

Abstract: This research investigates a promising antiviral compound based on polyprenols from Siberian silver fir (Abies sibirica). The physico-chemical characteristics of a preparation developed in aerosol form and an estimation of its protective efficacy against aerosol challenge of laboratory animals are presented. It is shown that (1) by using a simple ultrasonic disperser one can obtain aerosol of three formulations studied with about 70% of its mass accumulated in the size range below 1.8 microm; (2) 40-100% of ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…Apart from that, there are several studies that examine polyisoprenoid-containing bilayer lipid membrane models [35][36][37] and liposomal formulations [38]. All the accumulated research notwithstanding, there are still only a few commercial polyprenol formulations such as Ropren ® [39], Fortepren ® [3], and antiviral polyprenol aerosol [40] available on the market today, and thus we wished to explore the potential of such polyprenol preparations further.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from that, there are several studies that examine polyisoprenoid-containing bilayer lipid membrane models [35][36][37] and liposomal formulations [38]. All the accumulated research notwithstanding, there are still only a few commercial polyprenol formulations such as Ropren ® [39], Fortepren ® [3], and antiviral polyprenol aerosol [40] available on the market today, and thus we wished to explore the potential of such polyprenol preparations further.…”
Section: Discussionmentioning
confidence: 99%
“…There are two types of polyisoprenoids:the first is polyprenol, and the second is dolichol. Polyisoprenoids are not toxic, and polyisoprenoids are known to show some pharmacological activity, as anticancer (Kuznecovs et al, 2007), antidyslipidaemic (Singh et al, 2007), anti-influenza, and antiviral agents (Safatov et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…mairei. Polyprenols have anticancer (Kuznecovs et al, 2007), antidyslipidemic (Singh et al, 2007), anti-influenza and antiviral activities (Safatov et al, 2005). Several studies have demonstrated the hepatoprotective effects of polyprenols on patients with non-alcoholic steatohepatitis (Golovanova et al, 2010) and with acute or chronic hepatic injury induced by carbon tetrachloride (CCl 4 ) (Wang et al, 2008;Yang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%